2013
DOI: 10.1186/1472-6963-13-393
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a pay-for-performance system on timing to hip fracture surgery: experience from the Lazio Region (Italy)

Abstract: BackgroundA tariff modulation mechanisms has been introduced in some Italian regions with the aim of reducing inappropriate admissions and improving quality of care. In response to a regional act, hospitals in Lazio adopted a clinical pathway for elderly patients with hip fracture and introduced a compensation system based on the quality of health care, as in a pay-for-performance model. The objective of the present study was to compare the proportion of surgery for hip fracture performed within 48 hours of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 20 publications
0
22
0
1
Order By: Relevance
“…Nonwhite patients are at significantly greater risk of undergoing surgery at low-quality hospitals 31,32 . Investigators from Italy demonstrated that 2 policybased adjustments-public reporting of outcomes 33 and pay-forperformance compensation-significantly improved the quality of care for patients with hip fractures 34 . Both of these principles are present in the United States Affordable Care Act, indicating that strategic implementation of these policies could address disparities in care for patients with hip fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Nonwhite patients are at significantly greater risk of undergoing surgery at low-quality hospitals 31,32 . Investigators from Italy demonstrated that 2 policybased adjustments-public reporting of outcomes 33 and pay-forperformance compensation-significantly improved the quality of care for patients with hip fractures 34 . Both of these principles are present in the United States Affordable Care Act, indicating that strategic implementation of these policies could address disparities in care for patients with hip fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Pay-for-performance was found to improve quality and efficiency of cardiac rehabilitation (12). Also, a pay-for-performance model was associated with improved quality of care for older patients with hip fracture (13). Thus, rehabilitation characteristics of this study could be used as quality indicators and assessment criteria for pay-for-performance.…”
mentioning
confidence: 84%
“…Debates on the use of administrative databases routinely occur [12] and algorithms have been proposed to assess the disease status of large populations in Italy [52,53]. In general, Italian administrative databases have the potential to address important questions in post-marketing surveillance [8,54], epidemiology [12], quality performance and health services research [55]. In its annual review of drug utilization, the Italian Medicines Agency (AIFA), reported a list of 103 peer-reviewed publications of drug utilization studies performed in Italy [56].…”
Section: Significance and Conclusionmentioning
confidence: 99%